Targeted delivery of therapeutic oligonucleotides in pancreatic cancer - Iris Yang (Journal of Biology and Medicine - Peertechz Publications, 2022)
Currently, the most common treatment options for pancreatic cancer include chemotherapy, radiation, and surgery. These treatment options are not specific to the cause of the disease and therefore result in a large number of side effects including nausea, fatigue, hair loss, etc. The use of oligonucleotides may be a more efficient and safe method of cancer therapy. This mini-review will cover how oligonucleotides have been used to treat diseases in the past as well as different methods for delivery into the body and finally the applications of oligonucleotides in pancreatic cancer therapy.